Economic burden of diabetes mellitus in the WHO African region - Sambo Hama B; Kirigia Joses M; Sambo Luis G; Barry Saidou P (BMC, 2009)
Abstract Background In 2000, the prevalence of diabetes among the 46 countries of the WHO African Region was estimated at 7.02 million people. Evidence from North America, Europe, Asia, Latin America and the Caribbean indicates that diabetes exerts a heavy health and economic burden on society. Unfortunately, there is a dearth of such evidence in the WHO African Region. The objective of this study was to estimate the economic burden associated with diabetes mellitus in the countries in the African Region. Methods Drawing information from various secondary sources, this study used standard cost-of-illness methods to estimate: (a) the direct costs, i.e. those borne by the health systems and the families in directly addressing the problem; and (b) the indirect costs, i.e. the losses in productivity attributable to premature mortality, permanent disability and temporary disability caused by the disease. Prevalence estimates of diabetes for the year 2000 were used to calculate direct and indirect costs of diabetes mellitus. A discount rate of 3% was used to convert future earnings lost into their present values. The economic burden analysis was done for three groups of countries, i.e. 6 countries whose gross national income (GNI) per capita was greater than 8000 international dollars (i.e. in purchasing power parity), 6 countries with Int$2000-7999 and 33 countries with less than Int$2000. GNI for Zimbabwe was missing. Results The 7.02 million cases of diabetes recorded by countries of the African Region in 2000 resulted in a total economic loss of Int$25.51 billion (PPP). Approximately 43.65%, 10.03% and 46.32% of that loss was incurred by groups 1, 2 and 3 countries, respectively. This translated into grand total economic loss of Int$11,431.6, Int$4,770.6 and Int$ 2,144.3 per diabetes case per year in the three groups respectively. Conclusion In spite of data limitations, the estimates reported here show that diabetes imposes a substantial economic burden on countries of the WHO African Region. That heavy burden underscores the urgent need for increased investments in the prevention and management of diabetes.